Over-Voltage Prevention Solutions for 220 kV Distribution Substation to Enhance Power System Stability: A Case Study in Vietnamese Power System - Đoàn Đức Tùng (My University, 2017)
Over-Voltage Prevention Solutions for 220 kV Distribution Substation to Enhance Power System Stability: A Case Study in Vietnamese Power System
Keywords: Ngăn ngừa quá áp; Trạm biến áp 220kV; Ổn định hệ thống